Photochemical Degradation of Organic Matter in the Atmosphere. (30th April 2021) - Hu, Wei; Liu, Dandan; Su, Sihui; Ren, Lujie; Ren, Hong; Wei, Lianfang; Yue, Siyao; Xie, Qiaorong; Zhang, Zhimin; Wang, Zihan; Yang, Ning; Wu, Libin; et al.
Abstract: Organic matter in the gas‐phase and particles are important components of the atmosphere. Photochemical degradation is a major transformation pathway of atmospheric organic matter, which changes the atmospherically related life time and the environmental, climatic, and health‐related effects of organic matter, as well as biogeochemical cycles of elements. In addition to field observations and model simulations, laboratory experiments based on smog chambers and flow tubes are important approaches to study the photodegradation mechanisms and influencing factors of atmospheric organics. Isotopic composition is also a useful tracer for photodegradation processes of different organics, for example, carboxylic acids. In this article, research progress on photodegradation of several significant categories of organic pollutants which have aroused widespread concern currently, for example, polycyclic aromatic hydrocarbons, carboxylic acids, brown carbon, organosulfates/organonitrates, microplastics, and bioaerosols, are reviewed. The effects of different degradation mechanisms including photochemical reactions, heterogeneous aqueous reactions, and microbial degradation are also compared. Although the photodegradation of atmospheric organics has been studied to a certain extent, much more effort should be made to fill the large knowledge gap between the actual and simulated photodegradation processes. Abstract : Photochemical degradation is a major transformation pathway of atmospheric organic matter. It affects the fate of atmospheric organics and thus regulates the environmental, climatic, and health‐related effects of atmospheric organics as well as biogeochemical cycles of elements.